THE ROAD TO SUCCESS: THE CASE OF PERAK STATE ISLAMIC RELIGIOUS COUNCIL - S. Noor-Kaziemah; M. Rozaidy; Raman Noordin; Rasid Mail; Nur Shahida Ab Fatah (Journal of Islamic, Social, Economics and Development, 2021)
State Islamic Religious Councils (SIRCs) was established with the purpose tomanage Muslim affairs in Malaysia, especially for the underprivileged group throughimproving their social and economic welfare. Many criticisms were addressed by the publicand media on how well the SIRCs function and manage their finance. The critics do not comeempty without evidence of the real mismanagement cases reported by the public auditors andmedia. As scandals are prone to invite negative perceptions from the public, it also eclipsesthe organisations’ achievements by hyperbolically concentrating on the negative stories. As aresult, most literature related to the SIRCs has majorly focused on discussing the issues ratherthan reporting both sides of the stories, the issues or challenges and the achievements of theSIRCs. Hence, throughout the years, the SIRCs have been striving in improving theirperformances through engaging with many fruitful initiatives, which subsequently enhance theSIRCs’ ability to productively serve the Muslim community. The outcomes from theimprovements can be seen in many awards and recognitions received by the SIRCs.Highlighting the achievements of the SIRCs will not only increase the positive perceptions butmotivate other SIRCs to follow the same footsteps. Thus, the objective of this paper is to discussboth sides of the stories, i.e. challenges and achievements of Perak SIRC. The paper starts withan introduction of the roles and functions of Perak SIRC, then highlights the challenges ofPerak SIRC in carrying out its roles and continues with a discussion of the efforts undertakento improve their operations and the achievements gained through the effort. The study utilisesa case study method. The study found that Perak SIRC has a long history (since 1874) and hasachieved many milestones and awards for their excellent performance.